2010
DOI: 10.1002/mnfr.200900157
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake and depressive symptoms: A systematic review of observational studies

Abstract: The importance of research into the possible role of dietary intake in depressive symptoms is emphasized by the fact that diet is modifiable. We systematically reviewed observational studies investigating the association between dietary intake and depressive symptoms published in English as of December 2008. Using the PubMed database, 34 publications (23 cross-sectional, 10 prospective cohort, and 1 case-control studies) were identified. The number of subjects (n 5 80-27 111), age of subjects (15-97 years), di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
104
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(106 citation statements)
references
References 42 publications
2
104
0
Order By: Relevance
“…The dietary factors most commonly examined in observational epidemiological studies regarding this issue include nÀ3 polyunsaturated fatty acids, fish, folate, and other B vitamins, and most studies have found no association between dietary variables and depressive symptoms. 1 In our previous study, significant inverse associations were found between intake levels of fish, eicosapentaenoic acid, docosahexaenoic acid, and vitamin D and the prevalence of depressive symptoms during pregnancy, whereas a significant positive relationship was observed between the intake of saturated fatty acids and the prevalence of depressive symptoms during pregnancy in this population. 2 The possible role of dairy products and calcium in depressive symptoms has received much less attention; moreover, the findings have been inconsistent.…”
Section: Introductionmentioning
confidence: 56%
“…The dietary factors most commonly examined in observational epidemiological studies regarding this issue include nÀ3 polyunsaturated fatty acids, fish, folate, and other B vitamins, and most studies have found no association between dietary variables and depressive symptoms. 1 In our previous study, significant inverse associations were found between intake levels of fish, eicosapentaenoic acid, docosahexaenoic acid, and vitamin D and the prevalence of depressive symptoms during pregnancy, whereas a significant positive relationship was observed between the intake of saturated fatty acids and the prevalence of depressive symptoms during pregnancy in this population. 2 The possible role of dairy products and calcium in depressive symptoms has received much less attention; moreover, the findings have been inconsistent.…”
Section: Introductionmentioning
confidence: 56%
“…These nutrients might have favourable effects on psychological conditions through reducing serum homocysteine levels as well as through synthesis of monoamines including dopamine and serotonin in the brain (12) . Increased concentrations of serum homocysteine and decreased levels of dopamine and serotonin have been associated with increased risk of depressive disorders (10)(11)(12) . Folate and B vitamins are cofactors in the methylation process of homocysteine to methionine.…”
Section: Discussionmentioning
confidence: 99%
“…Biases in dietary reporting between men and women might explain this difference by sex. In addition, gonadal hormones might lead to differential responses to possible mediating factors (11) . The present study has several strengths.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations